2008
DOI: 10.1021/jp801630u
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ethylene by NiI(cyclam)+in Aqueous Solutions

Abstract: Ni(I)(1,4,8,11-tetraazacyclotetradecane)(+) reduces ethylene quantitatively to ethane plus butane (and hexane traces) in neutral aqueous solutions. A radical mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It should be pointed out that [Ni(I)L] + is reproduced in both reactions(20) and(21), and thus returned to the reaction mechanism. It should also be noted that the intermediate [Ni(II)L-CH(CO 2 -)CH 2 (CO 2 -)]is created in reaction (18) at 50% yield of the initial [Ni(I)L] + concentration.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…It should be pointed out that [Ni(I)L] + is reproduced in both reactions(20) and(21), and thus returned to the reaction mechanism. It should also be noted that the intermediate [Ni(II)L-CH(CO 2 -)CH 2 (CO 2 -)]is created in reaction (18) at 50% yield of the initial [Ni(I)L] + concentration.…”
mentioning
confidence: 75%
“…The disappearance of Ni(I)L + in the presence of maleate is much faster than in the presence of ethylene, the kinetics in the latter system were too slow to be studied in the linear accelerator. 20 At the observation wavelength of 340 nm three distinct timeresolved reactions are observed (Fig. 1 and 2).…”
Section: Reactions Of Ni(i)l + With Maleatementioning
confidence: 93%
See 1 more Smart Citation
“…* complexes with low valent transition metal ions. In a previous paper, it was reported that Ni I (1,4,8,11-tetraazacyclotetradecane) þ , NiðIÞL þ 1 , reduces ethylene quantitatively to ethane plus butane (and hexane traces) in neutral aqueous solutions [33]. A radical mechanism of reduction of ethylene was proposed.…”
Section: Introductionmentioning
confidence: 99%